Development of Student’s Innovation Skills through Extracurricular Activities - Wu, Yongshun; Fernando, Yudi (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
This study explores the development of students' innovation skills through extracurricular activities and its impact on their employability and academic performance. Innovation skills, comprising creativity, critical thinking, communication, and collaboration, are vital for students to adapt to change and contribute effectively to various domains. Extracurricular activities offer diverse platforms for students to enhance these skills, fostering innovation and preparing them for the dynamic professional landscape. Through participation in activities such as debate clubs, science fairs, and role-playing, students develop problem-solving abilities, teamwork, and creative thinking, essential for innovation. Moreover, extracurricular engagements complement formal education, providing life-wide learning experiences crucial for holistic development. The study also examines the correlation between extracurricular participation, psychological wellness, and academic achievement, particularly among underrepresented college students. Findings suggest that involvement in extracurricular activities fosters a sense of belonging, which positively influences academic performance. Additionally, RadGrad, a curriculum initiative, is discussed as a tool to integrate extracurricular experiences with academic goals, facilitating personalized learning pathways for students. Overall, this study underscores the significance of extracurricular activities in nurturing innovation skills, enhancing employability, and promoting academic success among students.